DRYING EFFECTS ON ULTRASONIC ASSISTED PHENOLIC YIELDS AND RETENTIVENESS OF ANTIRADICAL PROPERTIES OF COMMON CULINARY SPICES GINGER (ZINGIBER OFFICINALE) AND TURMERIC (CURCUMA LONGO): HPTLC AND GC - MS PROFILE FOR THEIR ACTIVE INGREDIENTS ASSESSMENT - Poonkuil, Nagarajan Leebanon; Raja, J. Dhaveethu (International Journal of Research -GRANTHAALAYAH, 2017)
The effect of drying on antiradical activity of Zingiber officinale (ginger) and Curcuma longo (turmeric) were studied by total phenolic content (TPC), total reducing power (TRP), 2,2’-azino-bis(3-ethyl benz thiazoline-6-sulphonicacid) (ABTS), 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and superoxide radical scavenging assays. Comparing fresh and dried rhizome, optimum antiradical activity was observed in dry ginger and in fresh turmeric. The drying phenomenon diminished the scavenging capacity especially in turmeric and also ginger rhizome was exhibited highest superoxide radical scavenging solely at fresh state. The extraction parameters were standardized for maximum recovery of phenolics. The Zingiberene of ginger and curcumin of turmeric rummaged the free radicals energetically.